Do we really need two sessions?: The use of a structured interview as a trauma cue reactivity paradigm - DeGrace, Sarah; Romero‐Sanchiz, Pablo; Yakovenko, Igor; Barrett, Sean P.; Tibbo, Philip; Cosman, Tessa; Atasoy, Pars; Stewart, Sherry H. (International journal of methods in psychiatric research, 2024)
Objectives Derived from classical conditioning theory and rooted in motivational mechanisms, cue reactivity paradigms (CRPs) are used in addictions research to measure participants' propensities for substance‐relevant responses (e.g., craving) during exposure to substance‐relevant cues (e.g., drug paraphernalia). CRPs are also useful in PTSD‐addiction comorbidity research, allowing the study of affective and substance‐relevant responses to trauma cues. However, studies using traditional CRPs are time‐consuming with high attrition rates due to repeat testing. Thus, we sought to test whether a single session semi‐structured trauma interview could serve as a CRP in terms of eliciting theorized cue exposure effects on craving and affect measures. Method Fifty regular cannabis users with trauma histories provided detailed descriptions of their most traumatic lifetime experience, and a neutral experience, according to an established interview protocol. Linear mixed models examined the effect of cue type (trauma vs. neutral) on affective and craving responses. Results As hypothesized, the trauma interview elicited significantly greater cannabis craving (and alcohol craving among the drinkers), and, greater negative affect among those with more severe PTSD symptoms, compared to the neutral interview. Conclusion Results suggest an established semi‐structured interview may function effectively as a CRP for use in trauma and addictions research.